A critique of terms and symbols in school mathematics - Vilkas, Robertas (Lietuvos matematikos rinkinys, 2023)
Criticism of some terms and symbols of school mathematics is presented, and recommendations are given. The problem of writing decimal fractions using a comma and the resulting semicolon when separating such numbers, which contradicts not only the international symbols of mathematics, but also the general rules of the Lithuanian language, is discussed separately. The incorrect use of the concept of an elementary event not only in schools, but also in universities, is discussed in more detail.
Keywords: notations; polynomial; elementary event; sample space; even number